CHARACTERISTICS OF MANGROVE VEGETATION DAMAGE BASED ON THE EXTENT AND SEVERITY OF INFESTATION ON PAHAWANG ISLAND, PESAWARAN REGENCY - Bela Apriandini; Machya Kartika Tsani; Inggar Damayanti; Indriyanto (Aquasains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2026)
Mangrove ecosystems on Pahawang Island are subjected to biotic, abiotic, and anthropogenic pressures that may compromise vegetation health. However, studies investigating organ damage based on the extent and severity of infestation in this area remain limited. This study aimed to analyze the characteristics of mangrove organ damage, the extent and severity of infestation, and the factors contributing to vegetation damage. Data were collected using a quantitative descriptive approach through field surveys. Observations were conducted in 23 plots across three sampling stations representing sparse (R. mucronata), moderate (R. mucronata), and dense (R. apiculata) mangrove stands. The assessed parameters included types of damage, the percentage of damaged organs, the extent of infestation, and the severity of infestation. The results identified ten types of damage affecting leaves, stems, and branches. The mean infestation extent across all stations was classified as very severe, reaching 92.69%. Despite the extensive occurrence of damage, the severity at the individual-tree level remained in the light-to-moderate category, with the highest severity recorded in the stems of mature trees (46.45%). These findings indicate that the mangrove vegetation retains a considerable capacity for recovery. Vegetation damage was associated with a combination of biotic factors, including defoliating insects, Littoraria sp., termites, and pathogenic fungi; abiotic factors, such as salinity, temperature fluctuations, and wave action; as well as anthropogenic pressures, including solid waste accumulation, tourism, and settlement activities. These findings highlight the need for integrated management of biotic disturbances and anthropogenic pressures to support the recovery and long-term health of the mangrove ecosystem on Pahawang Island.